Risk factors of 180-day rebleeding after management of blunt splenic injury without surgery and embolization: a national database study - Chung-Yen Chen; Hung-Yu Lin; Pie-Wen Hsieh; Yi-Kai Huang; Po-Chin Yu; Jian-Han Chen (World Journal of Emergency Surgery)
Abstract Purpose This study aimed to identify risk factors for rebleeding within 180 days post-discharge in blunt splenic injury patients managed without splenectomy or embolization. Materials and methods A retrospective analysis was conducted using Taiwan’s National Health Insurance Research Database. Adult patients aged ≥ 18 years with blunt splenic injury (ICD-9-CM codes 865.01–865.09) from 2000 to 2012 were included. Patients who died, underwent splenectomy (ICD-9-OP codes 41.5, 41.42,41.43, and 41.95) or transcatheter arterial embolization (TAE) (ICD-9-OP codes 39.79 and 99.29) on the first admission were excluded. The primary endpoint was rebleeding, which was identified if patients underwent splenectomy or TAE at 180 days after discharge. Multivariate logistic regression was used to identify risk factors, which were validated in a separate cohort. Results Of 6,140 patients, 80 (1.302%) experienced rebleeding within 180 days. Five significant risk factors were identified: age < 54 years (aOR 3.129, p = 0.014), male sex (aOR 2.691, p = 0.010), non-traffic accident-induced injury (aOR 2.459, p = 0.006), ISS ≥ 16 (aOR 2.130, p = 0.021), and congestive heart failure (aOR 6.014, p = 0.006). We generate Delayed Splenic Bleeding System (DSBS). Patients with > 2 points had significantly higher rebleeding rates (risk-identifying cohort: 2.2% vs. 0.6%, OR 3.790, p < 0.001; validation cohort: 2.6% vs. 0.8%, OR 3.129, p = 0.022). Conclusions Age < 54 years, male, non-traffic accident-induced injury, ISS ≥ 16, and congestive heart failure are risk factors of rebleeding within 180 days after discharge from treating blunt splenic injury without splenectomy or embolization. Despite limitations, this study underscores large-scale data’s role in identifying risks which can aid clinicians in prioritizing additional interventions during NOM.